Ascent and Decline of Native and Colonial Trading : Tale of Four Indian Cities - Seth, Vijay K. (London Sage, 2019)
"Ascent and Decline of Native and Colonial Trading: Tale of Four Indian Cities presents a vivid picture of how the British political regime reorganized the structure of the Indian economy to suit its own objectives. While doing so, the regime also affected the geographical distribution of economic activities. This resulted in the decline of native cities and prosperity of colonial cities. To reveal how the British colonial power brought about such changes in the Indian subcontinent, the book narrates the account of two pairs of native and colonial cities--Dacca and Calcutta from the eastern coast; and Surat and Bombay from the western coast. These were major centres of manufacturing, shared a common history and experienced the consequences of three different political dispensations--the Mughal Empire, the East India Company and the British Raj. It describes in detail how mutually beneficial relationships and interregional variations between these cities developed because of colonial restructuring. Due to its extensive coverage and analysis of the underlying phenomena, this book will prove indispensable for developing a deep understanding of Indian colonial and economic history."--Provided by publisher.
Economic environment during Mughal Empire -- Tale of four cities during Mughal Empire -- Economic environment during rule of East India Company -- Tale of four cities and the East India Company -- Economic environment during British Raj -- Tale of four cities and British Raj.
Includes bibliographical references and index.